Fragmented or cohesive transnational private regulation of sustainability standards? A comparative study. Issue 3 (27th May 2014) - Fransen, Luc; Conzelmann, Thomas
Abstract Literature on private regulation recognizes the proliferation of competing regulatory organizations and approaches in various industries. Studies analyzing why fragmentation arises so far focus on single‐case studies, the exploration of single variables, or variation in types of fragmentation. This article analyzes why in certain industries and for certain issues regulatory organizations proliferate, while in others a single regulatory organization emerges which covers the entire industry. Through a comparative case study of private regulation of sustainability standards in the forestry, clothing, IT‐electronics, and chemicals industries, we show how a combination of low industrial concentration, civil society involvement in governance, and stringent standards of a first‐moving regulator offer the strongest explanation for a fragmented private regulatory field, while high industrial concentration, business‐driven governance, and lenient standards of a first‐moving regulator lead to cohesive regulation.